2014
DOI: 10.1002/anie.201402751
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Robust Conductive Cellulose/Polypyrrole Composite Aerogels and Their Potential Application in Nerve Regeneration

Abstract: Nanostructured conductive polymers can offer analogous environments for extracellular matrix and induce cellular responses by electric stimulation, however, such materials often lack mechanical strength and tend to collapse under small stresses. We prepared electrically conductive nanoporous materials by coating nanoporous cellulose gels (NCG) with polypyrrole (PPy) nanoparticles, which were synthesized in situ from pyrrole monomers supplied as vapor. The resulting NCG/PPy composite hydrogels were converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(128 citation statements)
references
References 55 publications
2
125
0
1
Order By: Relevance
“…While conductive conduits have shown the ability to induce neuronal differentiation of PC12 cells in vivo [52] and promoting sciatic nerve regeneration in rat models by transmitting self- originated electrical stimulation between cells [53], in our study, we used external electrical stimulation on transplanted NCSCs to promote the Schwann cell differentiation and nerve regeneration. The polycaprolactone nanofiber we used is not a conductive material; however, the hydrogel + PBS filling is.…”
Section: Discussionmentioning
confidence: 99%
“…While conductive conduits have shown the ability to induce neuronal differentiation of PC12 cells in vivo [52] and promoting sciatic nerve regeneration in rat models by transmitting self- originated electrical stimulation between cells [53], in our study, we used external electrical stimulation on transplanted NCSCs to promote the Schwann cell differentiation and nerve regeneration. The polycaprolactone nanofiber we used is not a conductive material; however, the hydrogel + PBS filling is.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the mechanical properties of chemically crosslinked hydrogels, researchers have developed ingenious strategies, including nanocomposite hydrogels, double-network hydrogels, hybrid crosslinking hydrogels and tetra-polyethylene glycol hydrogels. [14][15][16][17][18][19][20][21][22] Recently, increasing research attention has been dedicated to enhancing the mechanical performance of physically crosslinked supramolecular hydrogels. One recent study demonstrated very tough physical hydrogels composed of polyampholytes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conductive hydrogel can provide an electrically efficient and adjustable cell growth platform. In addition, CNTs can be applied to electron-emitting fibrous polymers to improve mechanical strength [165]. Shin et al synthesized functional cardiac patches by seeding neonatal rat cardiomyocytes on CNT-incorporated photo crosslinkable gelatin methacrylate (GelMA) hydrogels (Figure 15) [166].…”
Section: Cardiac Tissue Engineeringmentioning
confidence: 99%